Climate change, transformative adaptation options, multiscale polycentric governance, and rural welfare in Oum Er-Rbia River Basin, Morocco: policy recommendations - Ait El Mekki, A.; Saleth, R. M.; Amarasinghe, Upali A.; Amarnath, Giriraj; Brouziyne, Youssef (International Water Management Institute, 2023)
This policy report is based on an analysis that delineates possible impacts pathways characterized by various configurations of climatic, economic, policy, technical, institutional, infrastructural, and welfare-related variables through which climate change’s impacts are transmitted ultimately on rural welfare at the grassroots level. The analytical framework provides an excellent operational context for evaluating the roles of Multiscale Polycentric Governance (MPG) in mediating and enhancing the climate resilience impacts of Transformative Adaptation Options (TAOs) both across regional scales and sectoral contexts. Empirical application of the framework to Morocco’s Beni Mellal region in the Oum Er-Rbia Basin shows linkages and synergies of TAOs and governance components that enhance the effectiveness of TAOs. Transition to effective forms of governance through institutional improvements can help the existing water institutions in the basin which are under extreme pressure due to the challenges of climate change.